Vibration Control and Structure Health Monitoring (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on new advances and developments in the topic of vibration control and structural health monitoring. In order to reduce the adverse impact of vibration on structures, vibration control and structure health monitoring have become increasingly important. In this reprint, frontier research topics in the following areas have been published: theory and computational methods of vibration control, materials and devices for vibration control, tests and applications of vibration mitigation or isolation techniques, structural health monitoring, vibration analysis, and tests and applications in relative fields.